The Role of Unfolded Protein Response in Coronavirus Infection and Its Implications for Drug Design - Xue, Mei; Feng, Li (Frontiers in Microbiology, 2021)
Coronavirus is an important pathogen with a wide spectrum of infection and potential threat to humans and animals. Its replication occurs in the cytoplasm and is closely related to the endoplasmic reticulum (ER). Studies reported that coronavirus infection causes ER stress, and cells simultaneously initiate unfolded protein response (UPR) to alleviate the disturbance of ER homeostasis. Activation of the three branches of UPR (PERK, IRE1 and ATF6) modulates various signaling pathways, such as innate immune response, microRNA, autophagy, and apoptosis. Therefore, a comprehensive understanding of the relationship between coronavirus and ER stress is helpful to understand the replication and pathogenesis of coronavirus. This paper summarizes the current knowledge of the complex interplay between coronavirus and UPR branches, focuses on the effect of ER stress on coronavirus replication and coronavirus resistance to host innate immunity, and summarizes possible drug targets to regulate the impact of coronavirus infection.